Evaluation of Belt Conveyor and Truck Haulage Systems in an Open Pit Mine Using Life Cycle Assessment - K. Awuah-Offei; D. Checkel; Askari-Nasab (Canadian Institute of Mining, Metallurgy and Petroleum, 2009)
Life Cycle Assessment (LCA) is an emerging environmental management tool for examining environmental impacts from cradle to grave. In this paper, LCA is used to evaluate the acidification potential (AP) and global warming potential (GWP) of belt conveyors and truck haulage systems in a surface gold mine using the ISO 14040 standards. The results show that, for AP, the truck system has 32 kg of equivalent SO2 per functional unit, compared to 8 kg for the conveyor system. However, for GWP, the conveyor has 2,820 kg of equivalent CO2 per functional unit, compared to 648 kg for the truck option.